(untitled) (The Pakistan Development Review, 2025)
The paper measures youths’ career aspiration index based on achievement, leadership, and educational aspirations and determines the role of career counselling and mentorship in career aspirations by applying heterogeneity bias-adjusted OLS on the primary data, collected through a questionnaire in the year 2020 from 1015 youth in Muzaffarabad, Azad Jammu and Kashmir, comprised of 42:58 male-female ratio. Findings show a 39 percent educational, 30 percent achievement, and 31 percent leadership aspirations index score with an overall index of 54 percent. The career plans, academic background, and mentorship appeared significant in shaping career aspirations among selective youth. It is suggested to hire qualified mentors and offer formal career counselling at institutions that can help in reinforcing youths’ motivation and efforts for better career choices that will ultimately bridge the labour market gaps in the area.